Exploiting rice diversity to uncover durable and broad-spectrum resistance - Bossa-Castro, Ana María, author; Leach, Jan E., advisor; Verdier, Valerie, committee member; Mosquera, Gloria, committee member; Argueso, Cristiana, committee member; Byrne, Patrick, committee member (Colorado State University. Libraries, 2018)
Rice is the staple food for human consumption and feeds over half the world's population. Major constraints towards a sustainable productivity of this cereal are losses caused by bacterial diseases, such as bacterial blight (BB) and bacterial leaf streak (BLS). Therefore, strategies aimed at increasing the global production of rice are essential. BB and BLS are caused by Xanthomonas oryzae pvs. oryzae (Xoo) and oryzicola (Xoc), respectively. This study aims to identify novel, broad-spectrum and durable sources of resistance to BB and BLS, and to pinpoint potential candidate genes for further characterization. We screened an indica rice Multi-parent Advanced Generation Inter-Cross (MAGIC) population, a novel mapping resource that allows high resolution detection for quantitative trait loci (QTL). A total of 14 disease resistance QTL effective against multiple X. oryzae strains were mapped, 11 confer resistance to both pathovars, i.e. broad-spectrum resistance (BSR), and three are pathovar-specific. We also detected specific alleles conferring disease resistance and susceptibility to these bacterial pathogens. Then, we combined diverse approaches to identify promising candidate genes, putatively involved in PAMP-triggered immunity (PTI) and effector triggered immunity (ETI), by (1) evaluating the presence and polymorphisms in defense-responsive cis-regulatory modules (CRMs) in gene promoters, (2) predicting gene promoters targeted by multiple X. oryzae strains, and (3) assessing the presence of SNP markers associated with resistance to X. oryzae strains. We also analyzed a cluster of MATH-BTB genes in a rice BSR QTL on chromosome 4 for polymorphisms between resistant and susceptible MAGIC lines. As a parallel approach to identify sources of durable resistance, the indica MAGIC population was also screened with an Xoo strain containing Tal7b, a transcription activator-like (TAL) virulence effector that is common to many Xoo strains. We mapped disease resistance QTL unique to this specific virulence factor and hypothesize that the mechanism of resistance conferred by one QTL is through a loss of susceptibility. BSR QTL and QTL specifically effective against virulence enhancing TALs may offer increased durability in the field. Because MAGIC lines are derived from elite cultivars, the use of identified QTL will be facilitated for the development of improved varieties.
Zip file contains supplementary tables.
Keywords: broad-spectrum resistance; QTL; Xanthomonas oryzae; MAGIC; TAL effector; Africa